Quality-of-life evaluation for advanced non-small-cell lung cancer: a comparison between vinorelbine plus gemcitabine followed by docetaxel versus paclitaxel plus carboplatin regimens in a randomized trial: Japan Multinational Trial Organization LC00-03 (BRI LC03-01) - Shinkai Tetsu; Kubota Kaoru; Origasa Hideki; Teramukai Satoshi; Tokoro Akihiro; Tada Harue; Kawahara Masaaki; Fukushima Masanori; Furuse Kiyoyuki (BMC Cancer, 2011)
Abstract Background A randomized trial of vinorelbine plus gemcitabine followed by docetaxel (VGD) versus paclitaxel plus carboplatin (PC) in patients with advanced non-small-cell lung cancer showed no difference in overall survival (median survival time: 13.6 versus 14.1 months) between the two treatment groups. We report here the results of quality-of-life (QOL) study initiated in the mid-course of this randomized trial. Methods The patients themselves assessed the Functional Assessment of Cancer Therapy (FACT)-Lung (FACT-L), FACT-Taxane and the Functional Assessment of Chronic Illness Therapy - Spirituality (FACIT-Sp) QOL instruments at baseline and 6, 12 and 18 weeks after the treatment. The primary endpoint was a comparison of total QOL score for each assessment instrument between the two groups. Results Sixty-eight patients from the trial (VGD, 34; PC, 34) who submitted baseline questionnaires and at least one questionnaire over the course of treatment were eligible. Longitudinal analysis showed a significant difference in slope of the FACT-Taxane score (p = 0.004) between treatment regimens over time, but no difference was found in FACT-L score (p = 0.311) and FACIT-Sp score (p = 0.466) between the two groups. Conclusions The significant difference in slope of FACT-Taxane score favored the VGD regimen. These data should be considered in treatment decision-making for patients with advanced non-small-cell lung cancer. Trial registration NCT00242983.